A study on the effects of tetracycline-impregnated surgicel on the microbial count of the periodontal sulci of white rats - Sison, Claudine May R.; Tripon, Carlo Pio M.
The use of Surgicel (oxidized regenerated cellulose) as a carrier device for prolonged release of antibiotic in the oral cavity was investigated. Twenty-eight albino rats were separated into four groups. The control group was left unadulterated. The placebo group had unadulterated Surgicel inserted into the periodontal sulci. The treatment group underwent tetracycline irrigation. The experimental group had tetracycline-impregnated Surgicel introduced into the sulci. The periodontal areas were swabbed and microbial counting was instituted at days 1, 3, 5, 8, and 10. All rats were placed under high-carbohydrate diet for the entire experiment. Results show that the treatment and the experimental rats showed similar counts which were significantly lower compared to the other groups for days 1 and 3. At days 5 onwards, however, the experimental group yielded significantly lower counts than the treatment group. This indicates that surgicel may be capable of prolonged release of antibiotics in the oral cavity and may thus prove to have potential use in periodontal therapy.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Antibiotics; Periodontal diseases -- Therapy